VD_FINDINFO HC / 2011 / 676 vom 2. November 2011 - VD Tribunal cantonal (2011)
ASSURANCE COMPLÉMENTAIRE, NÉCESSITÉ D'UN TRAITEMENT | 129 al. 1 Cst-VD, 143 al. 1 CPC (CH), 319 let. a CPC (CH), 321 CPC (CH), 326 CPC (CH), 405 al. 1 CPC (CH), 7 CPC (CH)